PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN KINERJA GURU TERHADAP PRESTASI SISWA - Sri Lestari (Satya Widya, 2016)
The purpose of this study is to determine how much influence school leadership and teacher performance on student achievement grade 6. Teachers play an important role for the success of students, but  the quality and loyalty of teacher performance leadership school. Until influenced by two factors greatly affect the achievement especially student learning outcomes Examination Schools. This research was conducted by quantitative descriptive approach. The data collection is done by using (1) questionnaires and (2) the study of document. Data were analyzed by calculating statistics using SPSS (Statistical Program Smart Solution) Ver.22 For Windows. Foreign objects are the elementary students grade 6 in District Tuntang. The results showed there is not significant relationship between   the leadership principals on student achievement, but there is a significant relationship between teaching performance of teachers to student achievement. Leadership Principal and teaching performance of teachers together have a strong influence on student achievement grade 6 elementary School in District Tuntang Semarang.